The Caries Experience in the Smoker and Non-Smoker among College Student - Azhar A. Hussein; Maha Issam; Hatham Yunis (Institute of Medico-legal Publications Pvt Ltd, 2021)
Dental caries is the scientific term for tooth decay or cavities. It is caused by specific types of bacteria. Theyproduce acid that destroys the tooth’s enamel and the layer under it, the dentin. The bacteria turn sugar andcarbohydrates (starches) in the foods we eat into acids. Smoking is also a global and national health problemand is one of the most significant health risks that impact all age groups.The Study Aims to investigate the effects of different tobacco smoking methods and their relation to dentalcaries in comparison to non-smoker students.Material and Method: A random sample of 336 students from Tikrit university aged 19-24 years, the samplegrouped to cigar, shisha, cigar and shisha together and non-smoker groups. Dental caries was recordedaccording to WHO criteria (1987) were decayed, missing and filled with permanent teeth (DMFS). The datawere analyzed as a descriptive statistic includes frequency, percentage, mean, and for statistical analysis ofthe data using T- test and one- way ANOVA test to detect the significance of the relation between variousvariable.Result: the result of this study showed that the severity of dental caries higher in smoking cigar and smokingshisha than in the non-smoking group with statistically highly significant.Conclusion Nicotine may be increasing the incidence and severity of dental caries. So that, nicotine mightbe considered as a risk factor for inducing of dental caries.